PHOTOMETRY OF COMET С/2009 P1 (GARRADD) BEFORE AND AFTER PERIHELION - Velichko, S. F.; Andreev, M. V. (Одеські астрономічні публікації, 2018)
During the period from September 2011 to February 2012, photometric observations of comet C/2009 P1 (Garradd) were performed on the 0.6-m telescope MC AMED at the peak Terskol (North-Caucasus). The paper presents an analysis of photometric observations of Comet C/2009 P1 (Garradd) obtained for heliocentric distances of 2.0-2.1 au before and 1.7-1.8 au after perihelion passage. The measurements of the comet were performed using a CCD camera SiTe003AB with narrow-band comet filters BC (λ4450/67Å), GC(λ5260/56Å), RC(λ7128/58Å) and C2(λ5141/118Å), CN(λ3870/62Å) HB-set (Farnham T., 2000). Observation data were obtained during 11 nights. According to the results of observations, the dust production Afρ (A’Hearn M.F. et al., 1984) of comet, the gas production of comet for molecules C2, CN using the Hazer model (Haser L., 1957), dust-to-gas ratio and color were calculated. The obtained results showed that the physical parameters of the comet are close to the average characteristics typical for dynamically new comets. .